Elevated serum growth differentiation factor 15 and decorin predict the fibrotic progression of metabolic dysfunction-associated steatotic liver disease - Jae Seung Chang; Jhii-Hyun Ahn; Moon Young Kim; Kyu-Sang Park (Scientific Reports, 2024)
Abstract Mitochondrial dysfunction with oxidative stress contributes to metabolic dysfunction-associated steatotic liver disease (MASLD) progression. We aimed to evaluate the fibrosis predictive efficacy of a novel non-invasive diagnostic panel using metabolic stress biomarkers. From a population-based general cohort, 144 subjects with MASLD were recruited in the development group and underwent magnetic resonance imaging-based liver examinations, anthropometric and laboratory tests. As an external validation group, 41 patients enrolled in a biopsy-evaluated MASLD cohort participated in this study. Liver fat content and stiffness were measured by magnetic resonance (MR) imaging-proton density fat fraction and MR elastography (MRE), respectively. Serologic stress biomarkers were quantitated by ELISA. Multivariate regression showed that waist-to-height ratio, growth differentiation factor-15 (GDF15), γ-glutamyltransferase, decorin, and alkaline-phosphatase were independent predictors of hepatic fibrosis (rank-ordered by Wald). The area under receiver-operator characteristics curve [AUROC (95% CI)) of the metabolic stress index for fibrosis (MSI-F) was 0.912 (0.85‒0.98) and 0.977 (0.92‒1.00) in development and validation groups, respectively. MSI-F also had better diagnostic accuracy (82.6‒92.4%) than other fibrosis indices in the both study cohorts. MSI-F consistently differentiated fibrosis severities across cohorts of MRE-evaluated general population and biopsy-proven patients with MASLD, while other indices showed no or less discrimination. MSI-F, as a novel non-invasive index based on a stress-stimulated protective hormone GDF15 and decorin, effectively predicted hepatic fibrosis. Furthermore, MSI-F may serve as pre-screening tool to increase the population that could be excluded from further evaluation, reducing unnecessary invasive investigations more effectively than other indices.